Hardware in the Loop Simulation of Active Front Wheel Steering control for yaw disturbance rejection - Khisbullah , Hudha; zakaria, Mohd Hafidz; tamaldin, noreffendy (Inderscience, 2011)
This paper introduces an Active Front Wheel Steering (AFWS) control for the purpose of reducing unwanted yaw motion. Side wind forces are considered to be the sources of yaw disturbance in this study. The proposed control strategy for the AFWS is a lateral directional control with yaw rate feedback. The AFWS controller was implemented on Hardware in the Loop Simulation (HiLS) using an AFWS test rig. From the simulation and experimental results, AFWS control is able to perform the task of yaw disturbance attenuation by providing additional steering correction for maintaining the original direction of the vehicle. Keywords: active front wheel steering; side wind force; yaw cancellation; HiLS; vehicle safety.